Radiation therapy for localized duodenal low-grade follicular lymphoma. (3rd August 2016) - Harada, Arisa; Oguchi, Masahiko; Terui, Yasuhito; Takeuchi, Kengo; Igarashi, Masahiro; Kozuka, Takuyo; Harada, Ken; Uno, Takashi; Hatake, Kiyohiko
Abstract: The aim of this study was to evaluate the initial treatment results and toxicities of radiation therapy for patients with early stage low-grade follicular lymphoma (FL) arising from the duodenum. We reviewed 21 consecutive patients with early stage duodenal FL treated with radiation therapy between January 2005 and December 2013 at the Cancer Institute Hospital, Tokyo. The characteristics of patients were: median age 62 years (range, 46–79 years), gender (male, 6; female, 15), clinical stage (I, 20; II 1, 1), histological grade (I, 17; II, 4). All patients were treated with radiation therapy alone. The median radiation dose was 30.6 Gy (range, 30.6–39.6) in 17 fractions. The involved-site radiation therapy was delivered to the whole duodenum. The median follow-up time was 43.2 months (range 21.4–109.3). The 3-year overall survival (OS), relapse-free survival (RFS) and local control (LC) rates were 94.7%, 79.3% and 100%, respectively. There were four relapses documented outside the treated volumes: two in the gastrointestinal tract (jejunum, terminal ileum), one in an abdominal lymph node (mesenteric lymph node) and one in the bone marrow. None died of the disease; one death was due to acute myeloid leukemia. No toxicities greater than Grade 1 were observed during treatment and over the follow-up time. The 30.6 Gy of involved-site radiation therapy provided excellent local control with very low toxicities. Radiation therapy could be an effective and safe treatment option for patients with localized low grade FL arising from the duodenum.